ISURF: a family of infinite-time surface flux methods. (22nd November 2016) - Morales, F; Bredtmann, T; Patchkovskii, S
Abstract: The computation and analysis of photoelectron spectra (PES) is a fundamental technique in atomic and molecular physics to study the structural and dynamical properties of a target system, and to gain insight into the process of its ionization. Since the first numerical solutions of the time-dependent Schrödinger equation (TDSE), numerous methods have been developed to extract PES from the calculated wave functions. However, most of these methods have severe limitations or are computationally very demanding. Here we present a new family of methods, based on the ideas of the so-called analytical Volkov continuation, or time-dependent surface flux (Ermolaev et al 1999 Phys. Rev. A60 483145 ; Ermolaev and Selin 2000 Phys. Rev. A62 015401 ; Tao and Scrinzi 2012 New J. Phys. 14 013021 ), that allows one to obtain fully-converged PES at the end of the laser pulse using either Volkov states or the exact scattering-states, and that has been implemented in the TDSE solver (Patchkovskii and Muller 2016 Comput. Phys. Commun. 199 153–69 ).